Influence of Olive Oil Mill Waste Amendment on Fate of Oxyfluorfen in Southern Spain Soils. Issue 7 (12th May 2015) - Calderón, María Jesús; Real, Miguel; Cabrera, Alegría; Koskinen, William C.; Cornejo, Juan; Hermosín, Mari Carmen
<x xml:space="preserve">Abstract</x> Oxyfluorfen herbicide residues have been previously reported in surface and ground water in the Guadalquivir river basin in Spain. Soil factors and processes (sorption, dissipation, and leaching) influencing the potential offsite transport of oxyfluorfen to surface and ground water were characterized in laboratory experiments for two soils from Southern Spain. The influence of olive‐oil mill waste amendment on the soil processes was also determined. Oxyfluorfen sorption in unamended soils was not significantly affected by soil active components (organic matter and clay fraction). However, a significant increase in soil sorption of the herbicide was observed upon amendment. Laboratory half‐life values for oxyfluorfen in unamended sandy clay loam and silty clay soils at 40% moisture content and 25°C were 29 and 19 days, respectively, and it increased by a factor of four upon amendment. Oxyfluorfen's mobility along soil profile increased with the amendment in leaching studies at 25°C, suggesting that dissolved organic matter of amendment can play an important role enhancing soil vertical movement of the pesticide. The increase in soil adsorption and persistence observed with olive‐oil mill waste amendment can promote its losses by runoff following winter application, whereas vertical movement of oxyfluorfen can be enhanced following spring application when olive‐oil mill waste amendment is also applied.